THE EFFECT OF JAKABA FERTILIZER ON THE GROWTH OF SPINACH PLANTS (Amaranthus viridis) - Khairunisa Khairunisa; Farhanah Shofwah Verina; Feby Djumaita Sari; Nadira Nadira; Azwir Anhar (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2025)
Green spinach is a vegetable with vitamin, protein, fat, carbohydrates, potassium, and important minerals such as calcium, phosphorus, and iron. Jakaba is one of the organic fertilizers. Jakaba fertilizer made from the fermentation of the first rice washing water, is a promising alternative to inorganic fertilizer. Rice washing water contains nutrients such as N, P2O5, K2O, and C-organic which play a role in plant growth. This study aims to determine the effect of Jakaba fertilizer on the growth of spinach (Amaranthus viridis). The method used in this study is the experimental method. By using a non-factorial Completely Randomized Design (CRD) consisting of 5 treatments, with 4 replications. The results of the study showed that Jakaba fertilizer has a major impact on the growth of spinach because it contains macronutrients as well as other micronutrients. The best spinach plant growth was shown in P3, which is 60 ml Jakaba/500 ml water.